2013
DOI: 10.1016/j.janxdis.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of anxiety disorder diagnoses in the military from 2000 to 2009

Abstract: a b s t r a c tThe objective of this study was to describe trends in the diagnostic rates for anxiety disorders (ADs) types in the U.S. military from 2000 to 2009. Data for the numbers of diagnosed cases for the first documented occurrence of ADs during ambulatory visits while serving in the military were obtained from the Defense Medical Epidemiology Database for all active duty service members and examined across branch of service and by gender. Results indicate that Anxiety Not Otherwise Specified (ANOS) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…These findings were expected, given that those respondents have experienced stress and overwork for many years and have become worn out over time. This observation has been demonstrated in other studies (3, 26,27).…”
Section: Discussionsupporting
confidence: 88%
“…These findings were expected, given that those respondents have experienced stress and overwork for many years and have become worn out over time. This observation has been demonstrated in other studies (3, 26,27).…”
Section: Discussionsupporting
confidence: 88%
“…A large literature documents the negative consequences of some military service experiences on veterans' mental health. Post-traumatic stress disorder (PTSD), anxiety, and depression are relatively common among military service members and veterans [52][53][54][55][56]. The etiology of these mental health conditions among veterans is complex and multifaceted, but it is often linked to traumatic experiences during combat.…”
Section: Plos Onementioning
confidence: 99%
“…Specifically, in the military field, it was observed that parachute jumping produces a large sympathetic modulation among paratrooper units [ 24 , 25 ], as well as in warfighters in asymmetrical combat environments [ 26 ], underground operations [ 27 ], special operation courses [ 28 ], survival maneuvers [ 29 ], or fighter jet pilots in combat flight maneuvers [ 30 , 31 ] and helicopters crews [ 32 , 33 , 34 ]. Chronic exposure to stressful events in military units was related to the prevalence of anxiety disorders and an increase in diagnoses over time in this millennium, with a prevalence of 0.8 per 100 service members for first service occurrence, followed by post-traumatic stress disorder (PTSD) at a rate of 0.5 out of every 100 [ 35 ]. In this context, the predominance of PTSD diagnosis has increased in recent years due to recent armed conflicts such as those occurring in Afghanistan or Iraq [ 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%